2023
DOI: 10.2340/17453674.2023.8479
|View full text |Cite
|
Sign up to set email alerts
|

Complications and risk factors of intramedullary bone lengthening nails: a retrospective multicenter cohort study of 314 FITBONE and PRECICE nails

Abstract: Background and purpose: Intramedullary bone-lengthening nails have become increasingly popular. The 2 most used and successful nails are the FITBONE and the PRECICE nails. Uniform reporting is lacking on complications of intramedullary bone-lengthening nails. The purpose was therefore to assess and categorize the complications of lower limb bone-lengthening nails and investigate risk factors.Patients and methods: We performed a retrospective review of patients operated on with intramedullary lengthening nails … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…No technical defect could be detected visually, but a jamming of the mechanical components at the beginning of the elongation seems likely without clear evidence. In 2023, Frost et al [ 15 ] found 32% device related complications per lengthening segment analyzing the Fitbone ® and Precice ® implants, 22 (per 314 segments) directly related to the distraction mechanism. Their device related complication rate is in line with the presented data of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No technical defect could be detected visually, but a jamming of the mechanical components at the beginning of the elongation seems likely without clear evidence. In 2023, Frost et al [ 15 ] found 32% device related complications per lengthening segment analyzing the Fitbone ® and Precice ® implants, 22 (per 314 segments) directly related to the distraction mechanism. Their device related complication rate is in line with the presented data of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the construction of an osmotic pump is much less complex than other lengthening mechanisms on the market (e.g. motorized or magnetic), the latter with a reported 32% device related complication rate [ 15 ]. Therefore, in comparison, the implant related failure rate should be less when distracting with the osmotic pump.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of 30 patients who had antegrade magnetic nail lengthening of the femur confirmed that earlier commencement of full weight-bearing accelerated consolidation of the regenerate bone during lengthening 43 . A multicenter study reviewed 314 lower-limb segments treated with internal lengthening nails to assess the complications associated with this surgical procedure 44 . The authors found a 53% complication rate and a higher risk of complications in the tibia compared with the femur as well as for >30-year-old age groups.…”
Section: Limb Lengtheningmentioning
confidence: 99%
“…Our outcome is binary, which is easier to interpret in odds-ratio terms: the effect of an explanatory variable is multiplicative on the odds and thus leads to an odds ratio. However, it should be noted that relative risk has been used in similar study designs [19].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In multivariable analysis, dislocation exceeding 10 mm was a risk factor for PPC (OR 6.3, CI 1. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%